Effects of Polyembryonic Seed Types on Early Seedling Growth of Duku (Lansium domesticum Corr) - Walingkas, Stanley A. F.; Tumewu, Pemmy; Rantung, Meity R.; Sintaro, Sanriomi; Paat, Frangky J. (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
Duku (Lansium domesticum Corr.) is an important tropical fruit tree in Indonesia, but the supply of uniform and vigorous planting material for orchard establishment remains limited. Polyembryony in duku seeds offers a potential source of clonal seedlings, yet the effects of different polyembryonic seed types and handling methods on seedling vigor are not well documented. This study evaluated early seedling growth of duku derived from zygotic and polyembryonic seeds under farmer managed nursery conditions in Eris Village, North Sulawesi. A randomized complete block design was used with five seed treatments and four replications: zygotic seed with a single embryo (Z1), intact polyembryonic seeds with two embryos (PU2), intact polyembryonic seeds with three embryos (PU3), polyembryonic seeds cut into two sections (PB2), and polyembryonic seeds cut into three sections (PB3). At the end of the nursery phase, number of leaves, plant height, stem diameter, leaf area, and root weight were recorded and analyzed by analysis of variance followed by the least significant difference test at the five percent level. Seed type significantly affected all traits. Zygotic seeds produced seedlings with the highest leaf number, plant height, stem diameter, leaf area, and root weight. Seedlings from cut polyembryonic seeds (PB2 and PB3) showed intermediate performance, with stem diameter and root weight close to those of zygotic seedlings. In contrast, seedlings from intact polyembryonic seeds with three embryos (PU3) had the lowest leaf number, leaf area, and root weight. These findings indicate that zygotic seeds remain the best option for producing vigorous duku seedlings, while sections of polyembryonic seeds, especially PB2 and PB3, can provide acceptable alternatives when zygotic seeds are limited or when clonal propagation is desired.   Keywords: duku; Lansium domesticum; polyembryonic seeds; seedling vigor; rootstock; nursery management